New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages - Ponder, W.f.; Zhang, W.-H.; Hallan, A.; Shea, M.e. (Zootaxa, 2019)
Species from artesian springs associated with the Queensland Great Artesian Basin that were previously included in the tateid genus Jardinella are included in three new genera, namely Eulodrobia, with six species, five of them new and all from the Eulo Supergroup; Springvalia, with one species from the Springvale Supergroup; and Carnarvoncochlea with two previously-described species, from the Carnarvon Supergroup. The genus Edgbastonia is extended to include eight previously described species, in addition to the type species, and four new species-group taxa from the Barcaldine Supergroup springs; all but the type species are included in the new subgenus Barcaldinia. Three new species from non-artesian springs in north Queensland are included in Edgbastonia, one of them tentatively. Two additional related new genera, both with a single new species, are described from outside the Great Artesian Basin; Conondalia from southeast Queensland and Nundalia from north-eastern New South Wales. The genus Jardinella, previously used for all the Queensland spring tateids, is here restricted to three species found in coastal rivers and streams in northeast Queensland. A molecular phylogenetic analysis using COI and 16S mitochondrial genes in combination suggests that the Queensland Great Artesian Basin taxa may be more closely related to the tateid genera Austropyrgus, Pseudotricula, Posticobia and Potamopyrgus than to the South Australian GAB taxa, thus indicating the separate origins of these two desert spring faunas.